2021
DOI: 10.7759/cureus.18500
|View full text |Cite
|
Sign up to set email alerts
|

Dengue: A Neglected Disease of Concern

Abstract: BackgroundDengue fever, more prevalent in Asia, is a highly neglected vector-borne disease. It has a varied presentation ranging from common fever to atypical presentation as encephalitis. This study aimed to analyze the demographic and clinical profile of dengue patients admitted to a tertiary care center in Tamilnadu. MethodologyThis retrospective study was performed by collecting patient data from the medical records department for the years 2012 to 2014. A total of 150 patients with 50 patients from each y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Bandyopadhyay et al also state that 11-20-year males were most affected age during the 2012 dengue outbreak in Kolkata [15]. Another study by Jisamerin et al demonstrates that fever was the primary symptom of DENV-positive patients, and most cases appeared from October to December in southern India [16]. One study modelled the role of anthropometric status on dengue in Colombian children in which DENV positivity was 60.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Bandyopadhyay et al also state that 11-20-year males were most affected age during the 2012 dengue outbreak in Kolkata [15]. Another study by Jisamerin et al demonstrates that fever was the primary symptom of DENV-positive patients, and most cases appeared from October to December in southern India [16]. One study modelled the role of anthropometric status on dengue in Colombian children in which DENV positivity was 60.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 1700 studies were retrieved from the database in the initial search, of which 278 were considered potentially eligible after reviewing the titles and abstracts. After reading the full text of the articles, 31 articles were eligible, of which 4 studies used the same dataset as the others, and 27 articles were included in this meta-analysis [15,20,[25][26][27][28][29][30][31][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The processes of study screening are shown in Fig 1, and the general characteristics of the included studies and the corresponding NOS scores are shown in Tables 1 and 2.…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%